Store Atmosphere Analysis and Shopping Emotion on Impulse Buying - Suhroji Adha; Irawan Irawan; Mira Nurhikmat; Yulaikah Yulaikah; Sapari Kahpi (Kontigensi : Jurnal Ilmiah Manajemen, 2019)
This study aims to determine the effect of (1) Store Atmosphere on Impulse Buying, (2) Sales Promotion on Impulse Buying, (3) the influence of Store Atmosphere and Sales Promotion on Shopping Emotion at Indomart Kampung Malangnengah Kel. Cijoropasir-Banten. This research is included in the type of causal research. The population in this study were all consumers from Indomart Kampung Malangnengah Kel. Cijoropasir Rangkasbitung-Banten, 99 samples were taken using non-probability sampling. Data was collected using a questionnaire, then analyzed using SEM analysis with the help of SmartPLS. The results of this study indicate that (1) Store Atmosphere has a significant effect on Impulse Buying as indicated by the value of tcount > ttable (9.253> 1.980) or P-value < (0.000 < 0.05), (2) Store Atmosphere has a significant effect on Shopping Emotion as indicated by the value of tcount > ttable (4.187> 1.980) or p-value < α (0.025 < 0.05), (3) Shopping Emotion has a significant effect on Impulse Buying is tcount > ttable (9.562> 1,980) or p-value < (0.000 < 0.05). and the mediation calculation that the value is 0.207 as shown by the path coefficient. The calculated t value of 4.369 is greater than the t table of 1.960, and the probability value of and Sig 0.00 < 0.05 is categorized, the effect is positive and significant, so that it means that the Store Atmosphere will affect impulse Buying through Shopping Emotion. (3) Shopping Emotion that has a significant effect on Impulse Buying is tcount > ttable (9.562> 1.980) or p-value < (0.000 < 0.05). and the mediation calculation that the value is 0.207 as shown by the path coefficient. The calculated t value of 4.369 is greater than the t table of 1.960, and the probability value of and Sig 0.00 < 0.05 is categorized, the effect is positive and significant, so that it means that the Store Atmosphere will affect impulse Buying through Shopping Emotion. (3) Shopping Emotion that has a significant effect on Impulse Buying is tcount > ttable (9.562> 1.980) or p-value < (0.000 < 0.05). and the mediation calculation that the value is 0.207 as shown by the path coefficient. The calculated t value of 4.369 is greater than the t table of 1.960, and the probability value of and Sig 0.00 < 0.05 is categorized, the effect is positive and significant, so that it means that the Store Atmosphere will affect impulse Buying through Shopping Emotion.